2008
DOI: 10.1002/jrs.2015
|View full text |Cite
|
Sign up to set email alerts
|

Raman and DFT study of hydrogen‐bonded 2‐ and 3‐chloropyridine with methanol

Abstract: Precise polarized Raman measurements of 2-chloropyridine (2Clpy) in the region 560-1060 cm −1 and 3-chloropyridine (3Clpy) in the region 680-1080 cm −1 at different concentrations in mole fraction of methanol were made to calculate the isotropic part of the Raman spectra, which has contributions only from vibrational dephasing. A detailed analysis of the Raman spectra was carried out to see the variation of peak position and linewidth. The dephasing is mode specific. The trigonal bending mode of 3Clpy has two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Our DFT calculations assign the following Raman bands to modes with ν(C–Cl) contributions: 628, 679, 796, 817, 832, and 1110/1098 cm −1 . In this range, only three bands at 724, 1080, and 1144 cm −1 have been assigned as ν(C–Cl) in pure 2‐chloropyridine …”
Section: Discussionmentioning
confidence: 99%
“…Our DFT calculations assign the following Raman bands to modes with ν(C–Cl) contributions: 628, 679, 796, 817, 832, and 1110/1098 cm −1 . In this range, only three bands at 724, 1080, and 1144 cm −1 have been assigned as ν(C–Cl) in pure 2‐chloropyridine …”
Section: Discussionmentioning
confidence: 99%
“…Concentration‐dependent Raman study gives clear idea of hydrogen bonding patterns in organic as well as aqueous solutions and helps to understand their solute–solvent interaction behavior. In some recent studies by our group, strong hydrogen bonding has been observed in aqueous solutions such as pyridine–water, pyrimidine–water and many other systems. In pyridines/pyrimidine + H 2 O mixtures, at higher water concentration the original reference peak of solute completely vanishes.…”
Section: Introductionmentioning
confidence: 99%
“…For the DFT calculations, the hybrid exchange functional wB97X‐D and the Gaussian type split basis set 6‐311++G(d,p) were used. DFT calculations have been demonstrated to contribute substantially for the understanding of experimental findings of ILs . The studied ion pairs and their water‐associated clusters were simulated without having any restrictions in the input geometries.…”
Section: Methodsmentioning
confidence: 99%